Palliative care in the pandemic: Have human rights been preferential? - Jain, Vinayak; Mujahid, Omer Mohammed; Rao, Pragna (Research and Humanities in Medical Education, 2021)
The skills that palliative care teams use every day at the bedside – symptom management, compassionate care, counselling of patients and families, calm and professional demeanour – are the same skills needed to treat patients with COVID-19. When it comes to humanitarian crises, the World Health Organization lists seven ethical principles that should direct palliative care. Unfortunately, many of these have been rendered impractical due to resource limitations and lack of training. Moreover, these ethical principles may guide individual patient encounters, but fall short when dealing with moral conflicts arising at a community or population level. We discuss how awareness of human rights can guide situations that call for tough decision-making in wake of this pandemic, and help us address some of these conflicts.